PERILAKU PENGGUNA SISTEM INFORMASI AKUNTANSI PADA PELAKU USAHA UMKM DALAM BISNIS E-COMMERCE - Naili Saadah; Moh Akil Nur Hakim; Ali Imron (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2022)
This study aims to examine the effect of the variable performance expectacy, effort expectacy, social influence, hedonic motivation, price value, habit and facilitating condition as independent variables and the behavior of users of E-commerce Accounting Information Systems as the dependent variable. Using a quantitative method by taking a sample of the MSMEs fostered in the city of Semarang, a total of 282 respondents were then analyzed by multiple linear regression using SPSS version 23 as an analytical tool. So the results of the study provide evidence that six of the seven variables used in this study, performance expectancy, effort expectancy, social influence, hedonic motivation, price value, habit, have a significant positive effect on the behavior of AIS users, only one variable that has no effect, namely Fascilitating Condition, it shows that facilities do not affect someone in implementing technology because nowadays almost everyone has a smartphone.